(untitled) (Bioagro, 2022)
The propagation of avocado plants by seed presents the disadvantage that the population obtained is heterogeneous and of variable productivity. Instead, those obtained through stems have homogeneous productive characteristics. In order to study improvements to propagation through stems, the effect of applications of Azospirilum brasilense and indole-3-butyric acid (IBA), to the stem of the avocado, either independently or in combination, was evaluated. The experiment was conducted in a completely randomized design, with four treatments (A. brasilense, AIB, A. brasilense plus AIB, and a control) with five repetitions. Under laboratory and growth chamber conditions, grafting the nurse seedlings var. Villacampa with cuttings of the var. Topa Topa was performed. After the formation of the tissue union, the plant was kept in dark conditions to obtain ethiolate shoots. Theses stems were subjected to a scraping of approximately 0.5 mm deep in the basal part, where the treatments were applied. The variables evaluated were plant height and stem diameter, along with fresh weight of foliage and roots. The results showed that the combination treatment better promoted all variables, significantly exceeding the control. It is concluded that the combination treatment influences the rooting of etiolated and layered avocado shoots.